Feasibility Test of Setumu Beach in Tanjungpinang City Riau Islands Province as a Rukyatul Hilal Location - Angkat, M. Arbisora; Maheran, Siti; Fauzan, Said Muhammad; Ramadhan, Wahyu; Syaputra, Adidtya (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
The basis for selecting Setumu Beach as the location of the rukyatul hilal because the failure to see the hilal in Bukit Cermin for 6 years. The Regional Office of Ministry of Religious Affairs of Riau Islands Province then conducted a survey to Setumu Beach and it was seen that Setumu Beach had wide visibility, an easily accessible location and there were various kinds of facilities and infrastructure. After further research, Setumu Beach is not supported by primary parameters, because the geographical conditions are blocked by trees, Soreh Island, highlands or small islands and lowlands at azimuth 240o-300o. Meanwhile, the weather conditions are also not supportive, because Tanjungpinang City has low air temperature, high humidity and rainfall, causing Tanjungpinang City to be more often in cloudy weather conditions and enter the wet month criteria. This is also supported by the results of rukyatul hilal report from Riau Islands Province Hisab Rukyat Team which always failed to see the hilal from 2021-2024 due to weather factors. Setumu Beach is supported by secondary parameters, because in terms of accessibility and facilities Setumu Beach is quite adequate. Because Setumu Beach is not supported by primary parameters and supported by secondary parameters, Setumu Beach is less suitable as a rukyatul hilal location.